2013
DOI: 10.1088/0031-9155/58/12/4357
|View full text |Cite
|
Sign up to set email alerts
|

Performance of KCl:Eu2+storage phosphor dosimeters for low-dose measurements

Abstract: Recent research has demonstrated that europium doped potassium chloride (KCl:Eu2+) storage phosphor material has the potential to become the physical foundation of a novel and reusable dosimetry system using either film-like devices or devices similar to thermoluminescent dosimeter (TLD) chips. The purposes of this work are to quantify the performance of KCl:Eu2+ prototype dosimeters for low dose measurements and to demonstrate how it can be incorporated into clinical application for in vivo peripheral dose me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Sm-doped nanocrystalline KCl was synthesised by a solid state reaction at a high temperature of 200 C for 3 hours with highquality precursors KCl (M/S Merck, AR grade, 99.95% pure) and SmCl 2 $6H 2 O (M/S Alfa Aesar, 99.5% pure). 17 During the synthesis, KCl was mixed with various concentrations of dopant precursor Sm such as 0.15, 0.25, 0.45, and 0.50 mol% to investigate the role of the Sm concentration for OSL applications. A nely ground homogenous mixture of prepared powder was subjected to a thermal treatment at 353-363 K for 3 hours to obtain ne nanophosphor.…”
Section: Materials Synthesismentioning
confidence: 99%
“…Sm-doped nanocrystalline KCl was synthesised by a solid state reaction at a high temperature of 200 C for 3 hours with highquality precursors KCl (M/S Merck, AR grade, 99.95% pure) and SmCl 2 $6H 2 O (M/S Alfa Aesar, 99.5% pure). 17 During the synthesis, KCl was mixed with various concentrations of dopant precursor Sm such as 0.15, 0.25, 0.45, and 0.50 mol% to investigate the role of the Sm concentration for OSL applications. A nely ground homogenous mixture of prepared powder was subjected to a thermal treatment at 353-363 K for 3 hours to obtain ne nanophosphor.…”
Section: Materials Synthesismentioning
confidence: 99%
“…KCl:Eu 2+ shows a linear response from zero to 60 Gy, and eventually saturates at about 500 Gy. Li et al (Li et al , 2013) recently reported that the same 1 mm- thick pellet sample is capable of detecting a doseto- water of 0.01 cGy, suggesting that KCl:Eu 2+ material yields a large dynamic range with comparable storage performance as traditional CR materials but superior radiation resilience.…”
Section: Resultsmentioning
confidence: 99%
“…The CCD of the Lynx scintillation detector measures discrete pixel counts ranging from 1 to 1000 and this will impose a maximum theoretical dynamic range of 1000:1. While this dynamic range is already respectable and useful for versatile dosimetry purposes, storage phosphors can confer an even higher dynamic range as they are able to measure absorbed doses‐to‐water that are as low as 0.01 cGy and high doses of up to 60 Gy without any saturation effects 18‐20,29,30 . Having a dosimeter with a wide dynamic range is important for the expedient measurement of proton halo effects as their doses are typically on the order of 0.1% of the peak proton dose 13 .…”
Section: Discussionmentioning
confidence: 99%
“…While this dynamic range is already respectable and useful for versatile dosimetry purposes, storage phosphors can confer an even higher dynamic range as they are able to measure absorbed doses-towater that are as low as 0.01 cGy and high doses of up to 60 Gy without any saturation effects. [18][19][20]29,30 Having a dosimeter with a wide dynamic range is important for the expedient measurement of proton halo effects as their doses are typically on the order of 0.1% of the peak proton dose. 13 Often, a proton spot will have to be delivered at a high dose for proton halo signals to be above background noise levels and a detector with an insufficient dynamic range will saturate easily.…”
Section: Dynamic Rangementioning
confidence: 99%